New Insights in Cardiac β-Adrenergic Signaling During Heart Failure and Aging - Lucia, Claudio de; Eguchi, Akito; Koch, Walter J. (Frontiers in Pharmacology, 2018)
Heart failure has become increasingly common within the elderly population, decreasing their survival and overall quality of life. In fact, despite the improvements in treatment, many elderly people suffer from cardiac dysfunction (heart failure, valvular diseases, arrhythmias or hypertension-induced cardiac hypertrophy) that are much more common in an older fragile heart. Since β-adrenergic receptor (β-AR) signaling is abnormal in failing as well as aged hearts, this pathway is an effective diagnostic and therapeutic target. Both heart failure and aging are characterized by activation/hyperactivity of various neurohormonal pathways, the most important of which is the sympathetic nervous system (SNS). SNS hyperactivity is initially a compensatory mechanism to stimulate contractility and maintain cardiac output. Unfortunately, this chronic stimulation becomes detrimental and causes decreased cardiac function as well as reduced inotropic reserve due to a decrease in cardiac β-ARs responsiveness. Therapies which (e.g. β-blockers and physical activity) restore β-ARs responsiveness can strongly ameliorate cardiac performance and outcomes during HF, particularly in older patients. In this review, we will discuss physiological β-adrenergic signaling and its alterations in both heart failure and aging as well as the potential clinical application of targeting β-adrenergic signaling in these disease processes.